Sistem Informasi Pembayaran Biaya Operasional Sekolah Berbasis Aplikasi - Tyas miyanti; Djumadi Sastro Wiyono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
The payment information system is a data processing system that will produce reports every period, which is once a month. The report will then be submitted to the leadership to find out the smoothness of payments for one month. The payment system functions to manage all payment data that is always changing through payment transactions.